Marketing in SMEs: a "4Ps" self-branding model. Issue 1 (7th March 2016) - Resnick, Sheilagh Mary; Cheng, Ranis; Simpson, Mike; Lourenço, Fernando
Abstract : Purpose: – The purpose of this paper is to explore the extent to which traditional marketing theory and practice can be applied in small- and medium-sized enterprises (SMEs) and consider how owner-managers perceive their own role in marketing within a small business setting. Design/methodology/approach: –A qualitative exploratory approach using semi-structured in-depth interviews amongst owner-managers of SMEs in the UK. Findings: – SME marketing is effective in that it embraces some relevant concepts of traditional marketing, tailors activities to match its customers and adds its own unique attribute of self-branding as bestowed by the SME owner-manager. Research limitations/implications: – The study was limited to the UK and to a small sample of SMEs and as such the findings are not necessarily generalisable. Originality/value: – A "4Ps" model for SME self-branding is proposed, which encompasses the attributes of personal branding, (co)production, perseverance and practice.